Effect of early intravenous calcium replacement after total thyroidectomy (Annals of Medical Research, 2024)
Aim: This study was to evaluate the need for postoperative calcium replacement in patients undergoing total thyroidectomy, to evaluate the effect of intravenous calcium therapy given in the early postoperative period regardless of serum calcium level and physical examination on the length of stay of the patients, parathormone levels, and the need for oral calcium after discharge.Materials and Methods: The files of 73 patients who underwent bilateral total thyroidectomy between January 2018 and July 2023 were retrospectively reviewed, and the demographic characteristics, anti-TG, anti-TPO, postoperative calcium, parathormone, thyroid gland weight of the patients were recorded. The effect of intravenous calcium replacement on calcium requirement, parathormone levels, and length of hospitalization was evaluated independently of calcium levels.Results: It has been observed that replacement is associated with long-term calcium requirement in patients who underwent bilateral total thyroidectomy and received intravenous calcium in the early period. The length of stay was found to be longer in patients who underwent calcium replacement.Conclusion: Various treatment methods are used to prevent hypocalcaemia. One of these treatment methods is early intravenous calcium replacement. In clinical practice, treatments given to prevent the development of complications and to discharge patients early may sometimes lead to the occurrence of complications that are tried to be prevented. The purpose of calcium replacement is to prevent the development of hypocalcaemia, to reduce the complication rate and to provide early discharge. It was evaluated that intravenous calcium replacement therapy, which was applied in the early period to prevent postoperative hypocalcaemia, caused patients to need longer-term calcium replacement and prolonged hospitalization.  It is important to avoid calcium replacement in the early period and to evaluate the physical examination findings along with the serum calcium level of the patients for replacement.
Keywords: Hypocalcaemia; Thyroidectomy; Calcium replacement